Towards improved structural stability and electrochemical properties of a Li-rich material by a strategy of double gradient surface modification. (July 2019) - Ding, Xiang; Li, Yi-Xuan; Wang, Shuo; Dong, Jie-Min; Yasmin, Aqsa; Hu, Qiao; Wen, Zhao-Yin; Chen, Chun-Hua
Abstract: The electrochemical properties of layered Li-rich oxide Li1.2 Ni0.13 Co0.13 Mn0.54 O2 (LLO) can be enhanced by a facile NaF surface modification. We have clarified by XPS, HR-TEM and HAADF-STEM analyses that the mechanism is the formations of a gradient coating layer Na1-x Lix F and a gradient LLO surface Li1.2-x Nax Ni0.13 Co0.13 Mn0.54 O2 via a Li + /Na + exchange reaction. The exchange reaction occurs at the Li-slabs of LLO down to a depth of less than 15 nm. After such a double gradient surface modification, the LLO displays markedly improved cycle life and rate capability as well as suppressed voltage decay. It exhibits a capacity retention of 85% beyond 1000 cycles at 10 C and a voltage decay of only 0.0021 V per cycle at 0.5 C, revealing great application prospects in energy storage materials. Graphical abstract: Image 1 Highlights: A double gradient surface modification is designed. Li + /Na + exchange reaction occurs at the Li slabs. Various analytical techniques are adopted to verify the mechanism.